The k43 gene, required for chorion gene amplification and diploid cell chromosome replication, encodes the Drosophila homolog of yeast origin recognition complex subunit 2. - Landis, G.; Kelley, R.; Spradling, A.C.; Tower, J. (Proceedings of the National Academy of Sciences of the United States of America, 1997)
Lethal alleles of the Drosophila k43 gene result in small or missing imaginal discs, greatly reduced mitotic index, and fragmented and abnormally condensed chromosomes. A female-sterile allele of k43 specifically reduces chorion gene amplification in ovarian follicle cells. k43 was cloned by chromosomal walking, and the identification of the k43 gene was confirmed by phenotypic rescue and sequence analysis of mutant alleles. The sequence analyses reveal that the k43 gene encodes the Drosophila homolog of the yeast origin recognition complex subunit 2 (Orc2p), a protein required for replication origin function and transcriptional silencing in yeast. These results suggest an evolutionarily conserved role for Orc2p in eukaryotic chromosomal DNA replication.